Paradigma baru konsep proteksi radiasi dalam pemeriksaan radiologi kedokteran gigi: dari ALARA menjadi ALADAIP - Fadhlil Ulum Abdul Rahman; Aga Satria Nurrachman; Eha Renwi Astuti; Lusi Epsilawati; Azhari Azhari (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: This article is aimed to widely share information and discuss further about the emerging transformation theories of the traditional radiation protection concept of ALARA into some more modern proposed concepts, particularly in dentomaxillofacial radiology. Literature Review: The concept of radiation protection in the use of X-ray modalities in the medical field has developed along with the development of science over past decades. The concept of ALARA which has been widely known for a long time and is used as a basic of theory or main reference in radiation protection policies in several countries or at the international level now becomes a traditional, conservative and invalid principle to apply. There are several emerging theories which are considered to be more valid and representative to replace the ALARA principle. Conclusion: Newer concepts of radiation protection that have developed, ALADAIP, are considered to be more precise and specific to be the main principle of radiation protection at this time, especially in the field of dentomaxillofacial radiology.